Theorizing a more radical approach to addiction through the lens of participatory spirituality. (2nd January 2020) - Eng, Peter
Abstract: This article examines the cultural attitude of reluctance in the United States, as reflected in recent opinion polls and federal budgets, toward agency spending in relation to addiction prevention, treatment, and research. The author posits that the prevalent spiritual lens, through which addiction is widely perceived, contributes to hesitancy in committing more to these areas of public funding. Its etiological interpretation of addiction, as a spiritual/moral disease that is innate to afflicted individuals, essentially releases culture and society from accountability for its prevalence. Further, publicity surrounding the New Recovery Advocacy Movement might lead to a complacent belief that a radical movement, addressing addiction on a broad, collaborative, and socioeconomic scale is already occurring. In order to widen the scope of spirituality as it generally pertains to addiction and accommodate the potentialities embedded in positive social change, the construct of spirituality needs to expand beyond the narrow and culturally entrenched notion of inner personal growth through individual effort. Therefore, this paper advances participatory spiritual theory as a means to integrate the reciprocity of socioeconomic and political factors as well as social engagement within a spiritual framework for recovery from addiction.